A geospatial approach for reducing uncertainty about the mitigation effect of seagrass on coastal erosion: A study case for the Greek coastline - Gonzalez, Alonso Gonzalez (2025)
Dissertation submitted in partial fulfilment of the requirements for the Degree of Master of Science in Geospatial Technologies